MODIFIKASI MESIN PENGGILING IKAN - Bilal Pratama, Muhammad; Sahril, Sahril; Sabila Rizky, Putra Pratama; Somawardi, Somawardi; Ramadhani Harahap, Dedy (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
Along with the development of the era, there have been many fish floss, kricu, kretek manufacturers that have used machines. However, there are still many machines that use combustion engines, which make workers uncomfortable because the engine is very wasteful of fuel and pollutes the air. And here the author wants to modify the wasteful and polluting combustion engine with an electric motor that is safe and does not pollute pollution. The implementation method used in making this final project is with the stages of the implementation process in the form of a flowchart including problem identification, data collection through surveys and literature studies, working drawings, machine manufacturing, machine assembly and testing. Based on the results obtained, a fish grinder machine uses a 6.5 HP electric motor with 3600 Rpm as the drive system. The transmission system used in this machine is a pulley and V-belt, and uses a horizontal system with a screw as a dough crusher. From the results of the machine test without load, all components in the animal feed crusher machine function properly. The machine test with a load shows that this machine is capable of making feed with a capacity of 55 kg / hour. This machine can be a solution for employees to overcome difficulties in the manual grinding process, as well as increase efficiency and productivity in the dough.